Lapsed, Augmented, and Eternal Christmases in the Theatre of Conor McPherson - Jordan, Eamonn (Hungarian Journal of English and American Studies, 2020)
Most commentators agree that many forms of theatre evolved from the ceremonies and rituals that existed across different societies and cultures at various historical moments. How ceremony and ritual might deepen, add significance or give substance to dramaturgical and performance practices remains one of the hallmarks of theatre traditionally and historically. No contemporary Irish writer has been so obsessed, fearful, trapped by, and even dependent on the idea or concept of this season of goodwill as Conor McPherson, in its anticipation, occurrence, and passing. His characters are often in fear of, trapped, or overwhelmed by Christmas and need to contest the hold of a funerary consciousness, predominantly a disposition of destructiveness, and counter-balance it with something more open and celebratory. In McPherson’s theatre, events surrounding Christmas become the manifestations of dream spaces, where nothing is predetermined, where chance can trump certainty, where chaos can trump order, where time is anything but linear and causal, where there is neither regulation of nor limits on the possible. McPherson’s dramas manipulate patterns, cycles, seasonalities, and rituals in order to suggest the possibility of other sorts of life rhythms, alternative consciousnesses, sensibilities and registers of collective and mutual aliveness. (EJ)